First record of the crested guan (Penelope Purpurascens) in the state of Guanajuato, Mexico - Bolaños Martínez, Ricardo; Sánchez-Cordero, Víctor; Gurrola Hidalgo, Marco A.; Iglesias Hernández, Jesús A.; Magaña-Cota, Gloria E.; Botello López, Francisco J. (Instituto de Ecología, A.C., 2010)
-